Perkembangan Permukiman Masyarakat Tionghoa di Palembang Pasca Kesultanan Palembang (1852-1942) (Sumbangan Materi Pelajaran IPS Kelas VIII di SMP Negeri 33 Palembang) - Eva Febrian; Yunani Hasan; Farida Farida (Criksetra: Jurnal Pendidikan Sejarah, 2015)
This study, entitled "The Development of Chinese Society settlements in Palembang Post Palembang Sultanate (1825-1942) as a contribution Lessons IPS Class VIII in Smp Negeri 33 Palembang". The research methodology used is the method of historical research with pengumupulan process data through documentation, interviews and studies kepustakaaan. The issues discussed in this study is what lies behind the establishment of settlements in the Chinese community in the Sultanate Raft house and how the development of Chinese society settlement after the end of administration in Palembang Sultanate (1825-1942). The results showed that the underlying settlement Raft Chinese community at home because of political policies of government of the Sultanate of Palembang. Then the development of Chinese society after the settlement of the Palembang Sultanate due to the Chinese community was given permission by the Dutch colonial administration to settle in the land and expand settlements. Palembang early settlement of the Chinese community in the mainland on the mark with the founding of the Chinese settlement in the Village and the Village 9/10 7 Ulu Ulu Palembang.